PENGARUH PENERAPAN PERMAINAN TRADISIONAL GOBAK SODOR DALAM MENINGKATKAN MINAT SISWA PADA PEMBELAJARAN SENI BUDAYA KELAS III DI SDN 39 RABADOMPU BARAT KOTA BIMA - Putri Aulia; Rakhmatul Ummah; Irmaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the traditional game of gobak sodor on students' interest in learning arts and culture. This study is a type of quantitative research using the pretest-posttest method. The instrument in this study uses a questionnaire on students' learning interests. The data analysis technique used in this study is descriptive quantitative. Based on the results of the analysis, the pretest data, getting an average percentage increase from pre-test to post-test is around 49.80% overall there is an increase in students' learning interest almost half higher than before the treatment, showing good criteria. Meanwhile, from the posttest results, getting a percentage shows good criteria and can be used. Based on this analysis, it can be concluded that the effect of the gobak sodor game on students' interest in participating in art learning can be used and applied as an influence on learning interest in learning arts and culture in grade III students of SDN 39 Rabadompu, Bima City.